Evaluación de un proceso para la recuperación de Bases lubricantes contenidas en los aceites lubricantes usados (2020)
In order to carry out this project, the evaluation of the process for the recovery of lubricant bases was carried out and this was carried out in the laboratories of the Lubrisol de Colombia Ltda. Company. Therefore, to begin the determination of physical properties and chemical to the used oil sample according to NTC 3382 which are: viscosity at 40 ℃, viscosity at 100 ℃, density, API gravity, spark point, flash point, viscosity index, color, content of wear metals. Subsequently, the most suitable process for the recovery of the lubricant base was evaluated through a detailed investigation of the existing processes for the recovery of bases found in the literature and in databases such as knovel, sciencedirect, onepetro among others, From this, a pugh matrix of the processes found was made and two were taken according to the criteria selected as cost, risks, raw material, to carry out the process selected experimentally in the laboratory of the support company.